SIMULATION OF THE PRE- AND POST-TRANSIT TIME OF FLIGHT METHODS IN AMORPHOUS SILICON-LIKE. N+-I-P+ -CELLS SIMULATION DES METHODES DE PRE- ET POST-TRANSIT DE LA TECHNIQUE TEMPS DE VOL POUR LES CELLULES N+-I-P+ EN MATERIAU DE TYPE a-Si:H. - MEFTAH, AM.; MEFTAH, AF.; MERAZGA, A. (Courrier du Savoir; Vol. 3 (2003): Courrier du Savoir)
In this paper, we study, by numerical simulation, the Transient Photocurrent (TPC) resulting from the application of the 'Time Of Flight' (TOF) technique to a-Si:H n+-i-p+ cell by using a typical Density Of States (DOS) of amorphous silicon. The preand post-transit methods, currently used to probe the energy distribution of localised states, are then applied to reconstruct the proposed DOS from the simulated TPC. We demonstrate that the two methods of reconstruction are complementary and provide an efficient tool of determining the transit time.